2015
DOI: 10.1177/1479164115590559
|View full text |Cite
|
Sign up to set email alerts
|

Borderline ankle–brachial index is associated with increased prevalence of micro- and macrovascular complications in type 2 diabetes: A cross-sectional analysis of 12,772 patients from the Joint Asia Diabetes Evaluation Program

Abstract: Borderline ankle-brachial index is increasingly recognised as a marker of cardiovascular risk. We evaluated the impact of borderline ankle-brachial index in 12,772 Chinese type 2 diabetes patients from the Joint Asia Diabetes Evaluation Program between 2007 and 2012. Cardiovascular risk factors, complications and health-related quality of life were compared between patients with normal ankle-brachial index (1.0-1.4), borderline ankle-brachial index (0.90-0.99) and peripheral arterial disease (ankle-brachial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…In addition, a prospective study in African‐Americans with T1DM found that DR severity at baseline was a significant independent risk factor for the incidence of lower extremity arterial disease, defined as present if a patient has had an amputation or angioplasty for poor circulation, or if there is an absence of major arterial pulse in the legs . However, in patients with T2DM, a borderline ABI (0.90‐0.99) has been identified as an independent predictor of DR and other microvascular and macrovascular complications …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a prospective study in African‐Americans with T1DM found that DR severity at baseline was a significant independent risk factor for the incidence of lower extremity arterial disease, defined as present if a patient has had an amputation or angioplasty for poor circulation, or if there is an absence of major arterial pulse in the legs . However, in patients with T2DM, a borderline ABI (0.90‐0.99) has been identified as an independent predictor of DR and other microvascular and macrovascular complications …”
Section: Resultsmentioning
confidence: 99%
“…93 However, in patients with T2DM, a borderline ABI (0.90-0.99) has been identified as an independent predictor of DR and other microvascular and macrovascular complications. 94…”
Section: Peripheral Complicationsmentioning
confidence: 99%
“…One study showed that IAND could better predict both overall and cardiovascular mortality than IAD in elderly patients [3]. ABI exhibits better association with cardiovascular outcomes than IAD in patients with type 2 diabetes [25]. However, no study has reported the comparison between IAND and IAD in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing hemodialysis, high PWV and low ABI are significantly associated with mortality [33]. Therefore, ABID and IAND could be more influenced by endothelial dysfunction, systemic atherosclerosis, calcification burden, and arterial stiffness than IAD, which may be related to more frequent PAD in the lower extremities [25,26,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The multiethnic study of atherosclerosis indicated that lower arterial elasticity predicted faster kidney function decline in subjects with eGFR>60ml/(min·1.73m2). In addition, renal function also declined as ABI decreased [22]. These results revealed the intimate correlations of renal function with various cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 89%